2012
DOI: 10.3945/jn.111.155937
|View full text |Cite
|
Sign up to set email alerts
|

Serum Retinol Is Associated with Stage of Pregnancy and the Acute Phase Response in Pregnant Women in Guinea-Bissau,

Abstract: Vitamin A deficiencies in pregnancy may impair the health of the mother and the growth, development, and later health of her offspring. However, the understanding of the variability of micronutrient status markers during pregnancy is limited. We measured serum retinol and β-carotene and the acute phase proteins C-reactive protein (CRP) and α(1)-antichymotrypsin (ACT) in 738 pregnant women in a cross-sectional study in Guinea-Bissau, West Africa. Gestational age ranged from 7 to 42 wk (mean ± SD = 23 ± 7 wk). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 22 publications
8
25
1
Order By: Relevance
“…In the present study, even using CRP values to control for the possible effect of an infectious process, the results were close, with VAD being diagnosed in 4.5% of women with CRP levels <5 mg/L and in 7.4% of those with CRP levels ≥5 mg/L. CRP is an acute phase protein in the inflammatory process, participating predominantly in innate immune response [35,48]. Nonetheless, an increase in CRP levels may occur in many other situations as well as in the presence of infection, including during a normal or physiological pregnancy when levels reflect the adaptations needed to support the fetus.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In the present study, even using CRP values to control for the possible effect of an infectious process, the results were close, with VAD being diagnosed in 4.5% of women with CRP levels <5 mg/L and in 7.4% of those with CRP levels ≥5 mg/L. CRP is an acute phase protein in the inflammatory process, participating predominantly in innate immune response [35,48]. Nonetheless, an increase in CRP levels may occur in many other situations as well as in the presence of infection, including during a normal or physiological pregnancy when levels reflect the adaptations needed to support the fetus.…”
Section: Discussionsupporting
confidence: 56%
“…The findings reported here are similar to those found in China, where a frequency of VAD of 5.2% was found in a group of 1209 pregnant women evaluated in 150 urban or rural areas between 2013 and 2014 [30]. Compared to the present findings, other studies conducted in developing countries using the cut-off point of <0.70 μmol/L reported much higher prevalence rates of VAD in pregnant women: 24.6% in 3270 pregnant women in Iran [31], 20% in a sample of 80 women in Egypt [32], 18.5% in 200 women in Bangladesh [33], 15.8% in 101 women in Nigeria [34], 13.8% in 738 women in Guinea-Bissau [35], and 10.6% in 160 pregnant adolescents in Venezuela [18]. However, only the sample sizes used in the studies conducted in China, Iran, and Guinea-Bissau were large enough to yield robust data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with regard to pregnancy there are conflicting results, confirming this assumption [23,34], as well as indicating ROH-RBP4 ratio > 1 [43], even if we found no report considering the ROH/RBP4 molar ratio in the first trimester of pregnancy. The only paper dealing with ROH in the first trimester found a ROH concentration linearly decreasing from the first trimester to the end of pregnancy [44].…”
Section: Discussionmentioning
confidence: 98%
“…However, the baseline serum retinol levels of the study control and supplemented groups were higher than those found in India [31], Africa, [32,33], and Ethiopia [34] as these countries have high prevalence of vitamin A deficiency, and in Germany [35], probably because of the very different sample size. On the other hand, Yang et al [36] reported a higher level of serum retinol possibly because of different diets of the two samples and sampling methods.…”
Section: Discussionmentioning
confidence: 66%